Imperative Utterances in Shopee Advertisements - Candra Wartina; Kurnia Tika; Rahimi Munthe; Juli Yani; Melinda Aulia; Ridho Kurniawan (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The rapid growth of e-commerce applications has intensified competition among various platforms. As new e-commerce platforms emerge, advertising strategies have become critical for capturing consumer attention. Language elements in advertisements play a vital role, as the rhetorical style used can significantly influence consumer interest. This study aims to analyze the effectiveness of using imperative speech acts in Shopee advertisements. A qualitative method was employed in this research, utilizing documentation from selected advertisements. The study analyzed three Shopee advertisement videos to identify and assess the types of imperative speech acts used. The findings reveal that Shopee advertisements prominently feature direct and literal imperative speech acts. These acts serve to encourage specific actions, such as downloading the app, making purchases, or participating in promotional campaigns, thus enhancing audience engagement. The analysis indicates that the use of imperative speech acts in Shopee advertisements is highly effective. The platform's ability to compel consumers through clear and action-oriented language contributes to its success in the competitive e-commerce market. The effectiveness is evident from the widespread adoption of the Shopee application among consumers. This study highlights the importance of strategic language use in advertising and underscores how tailored rhetorical approaches can influence consumer behavior, solidifying Shopee’s position in the e-commerce industry.